Pengaruh Kreativitas dan Keaktifan Berorganisasi terhadap Kesiapan Kerja pada Mahasiswa Sekolah Tinggi Ilmu Pastoral Keuskupan Agung Kupang dengan Soft Skill sebagai Variabel Intervening - Cunha, Adilson Barros Da; Erom, Kletus; Talok, Damianus; Yasinto, Yulius; Naen, Alfons Bunga (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research uses soft skills as an intervening variable to examine how students at the College of Pastoral Sciences of the Archdiocese of Kupang are prepared to enter the world of work in terms of creativity and organizational activities. The approach in this research is a quantitative approach. The population and sample in this research were 60 STIPAS students of the Archdiocese of Kupang. Meanwhile, the data analysis used was Partial Least Square (PLS). The results of this research reveal that there is a significant influence between the creativity and soft skills variables on the work readiness variable, but the organizational activity variable has no significant effect on soft skills. The soft skill variable is influenced by the creativity and organizational activeness variables. The soft skills variable is able to mediate the influence of the creativity and organizational activity variables on work readiness.